Intravenous thrombolysis for acute ischaemic stroke in young adult patients. - Poppe, A; Buchan, A; Hill, MD (2009)
BACKGROUND: Intravenous tissue plasminogen activator (IV tPA) has been studied primarily in patients over age 50. We sought to describe baseline differences in adult patients < or = 50 years-old taken from a large prospective cohort of acute stroke patients treated with intravenous tPA (IV tPA) and to determine whether outcomes differed for this population. METHODS: Data (n = 1120) prospectively collected from the Canadian Alteplase for Stroke Effectiveness Study (CASES) were reviewed and patients aged < or = 50 years-old (n = 99) were compared with those aged > 50 years (n = 1021) with regards to baseline characteristics, symptomatic intracerebral haemorrhage (sICH), functional outcome at 90 days and death. RESULTS: Nine percent of patients were < or = 50 years-old. Among patients aged < or = 50 years, 40.4% were women and median age was 42 +/- 6.1 years (range 20 to 50). They had significantly more current cigarette use but fewer other vascular risk factors than older patients (p < 0.05) and their baseline median NIHSS score was lower (13 versus 15, P = 0.001). Although this group was more likely to have a favourable 90-day outcome, multivariable regression confirmed that age < or = 50 years, while independently associated with a decreased risk of death (RR 0.36, 95% CI 0.14 to 0.95), was not itself predictive of favourable 90-day outcome or decreased risk of sICH. CONCLUSIONS: Adult patients < or = 50 years-old had fewer medical co-morbidities and a modestly lower baseline median NIHSS score than their older counterparts. Age < or = 50 years was independently associated with a decreased risk of death but not with favourable outcome or risk of sICH.